Availability and readability of patient education materials for deprescribing: An environmental scan - Fajardo, Michael Anthony (Br J Clin Pharmacol, 2019)
AIMS: To identify and evaluate content and readability of freely available online deprescribing patient education materials (PEMs). METHODS: Systematic review of PEMs using MEDLINE, Embase, CINAHL, PsycINFO and The Cochrane Library of Systematic Reviews from inception to 25 September 2017 to identify PEMs. Additionally, deprescribing researchers and health professionals were surveyed to identify additional materials. Known repositories of materials were searched followed by a systematic Google search (22–28 January 2018). Materials were evaluated using an approach informed by the Patient Education Material Assessment Tool and the International Patient Decision Aids Standards Inventory. Readability of text‐based materials was assessed using the US‐based Gunning–Fog Index and Flesch–Kincaid Grade level. RESULTS: Forty‐eight PEMs were identified. PEMs addressing deprescribing of medications for symptom control (81%) were most common. Preventative medications were rarely addressed and material (39%) focused on older people. Only 37% of PEMs provided information about both potential benefits (e.g. reducing risk of side effects) and harms (e.g. withdrawal symptoms, increased risk of disease) of deprescribing, while 40% focussed on benefits only. Readability indices indicated an average minimum reading level of Grade 12. Option Grids and Decision Aids (mean reading level below Grade 10) were most suitable for people with average literacy levels. CONCLUSIONS: Over 1/3 of deprescribing PEMs present potential benefits and harms of deprescribing indicating most of the freely available materials are not balanced. Most PEMs are pitched above average reading levels making them inaccessible for low health literacy populations.